2018
DOI: 10.1007/s10995-018-2511-4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Child and Adolescent Hospital Admission Rates in Queensland, Australia, 1995–2011: A Comparison of Coal Seam Gas, Coal Mining, and Rural Areas

Abstract: Objectives At present, coal seam gas (CSG) is the most common form of unconventional natural gas development occurring in Australia. Few studies have been conducted to explore the potential health impacts of CSG development on children and adolescents. This analysis presents age-specific hospitalisation rates for a child and adolescent cohort in three study areas in Queensland. Methods Three geographic areas were selected: a CSG area, a coal mining area, and a rural area with no mining activity. Changes in are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Ewald estimated that monetary public health costs of sulfur dioxide emissions from coal power plants in New South Wales far exceeded the pollution fees paid by existing generators. Werner and colleagues reported that children's hospital admission rates in Queensland were highest in an area of coal seam gas development, followed by a coal mining area, and were lowest in a rural area without these features.…”
mentioning
confidence: 99%
“…Ewald estimated that monetary public health costs of sulfur dioxide emissions from coal power plants in New South Wales far exceeded the pollution fees paid by existing generators. Werner and colleagues reported that children's hospital admission rates in Queensland were highest in an area of coal seam gas development, followed by a coal mining area, and were lowest in a rural area without these features.…”
mentioning
confidence: 99%
“…Additionally, age-specific studies found increasing “Blood/immune” disease admission rates in a CSG study area compared to the other study areas and decreasing rates for one child/adolescent age group [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…A previous ecological study compared all-age hospitalisation rates in the same CSG study area used here to coal mining and rural/agricultural study areas and found that hospitalisation rates for “Blood/immune” diseases, “Neoplasms”, and “Congenital” outcomes increased in the CSG study area relative to the hospitalisation rates in the other study areas [ 19 , 37 ]. Additionally, age-specific studies found increasing “Blood/immune” disease admission rates in a CSG study area compared to the other study areas and decreasing rates for one child/adolescent age group [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While such moves are often not universally well received in the community (Tlozek, ), the challenge is that as an industry, CSG is still subject to ongoing review over the nature of its impacts on society and the environment (Cui et al ., ; Fleming & Measham, ; Werner et al ., ). In addition to being technologically new, it is also case‐specific with respect to the interplay of different community stakeholder groups in discussions over best practice management.…”
Section: Reading Relational Csg Space In the Hunter Valleymentioning
confidence: 97%